Prestasi Belajar PAI Materi Wudhu melalui Metode Demonstrasi pada Peserta Didik Kelas I Sekolah Dasar - Asni Faisah; Reizal Putra (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
This study aims to determine whether the demonstration method can improve student learning achievement in wudhu material among first-grade students at SDN 21 Kampun Kajai. This study uses the demonstration method by demonstrating or showing students the process and situation being studied so that learning is more memorable and profound for students. This research is action research with 3 cycles through 4 stages, namely planning, implementation, observation, and reflection. The subjects of this study were 25 students. The hypothesis proposed is that if the demonstration method is used properly, it can improve the achievement of students in Islamic Education subjects in grade I at SDN 21 Kampung Kajai in the 2024/2025 academic year. The success indicator is 75% with a minimum passing grade of 75. The data collection technique is observation. The data analysis technique uses a formula to determine the average score and learning presentation in cycle I of 44% or 11 students with a minimum passing grade of 75, Cycle II was 56% or 14 students with a minimum passing grade of 75, and Cycle III was 81% or 22 students for the material on the pillars of wudu and 87.5% or 25 students for the material on the sunnah of wudu with a minimum passing grade of 75. The increase in student learning achievement from cycle I to cycle II was 12% with a minimum passing grade of 75, while the increase in achievement from cycle II to cycle III was 25% for the material on the pillars of wudhu and 31.5% for the material on the sunnah of wudhu.